EPISTEMOLOGI PLURALISTIK PENDIDIKAN AGAMA ISLAM PERSPEKTIF ABDURRAHMAN WAHID - Jazirotu Zamzam; Mahasin Haikal (Yupa: Historical Studies Journal, 2023)
The diversity that exists in Indonesia is undoubtedly unique, in fact Indonesia has diversity in several aspects, of course this has become a separate icon for various regions of Indonesia, especially in the variety of religions and thoughts. Today, every problem that exists in Indonesia, be it in the economic, political, cultural, racial and ethnic aspects, occurs because of moral degradation and the narrowness of thinking about national democracy. So that this is also an influence on the development of education in Indonesia, especially in religious education. According to Abdurrahman Wahid's (Gus Dur) pluralistic thoughts and views, religious education must pay attention to religious and cultural diversity in society, and must not ignore or marginalize views that differ from the views of the majority of religions. In this study, researchers focus on how pluralistic epistemology in Islamic religious education is from Abdurrahman Wahid's perspective. The method in this study uses qualitative research by presenting data in a descriptive analysis manner compiled through literature review and literature study. The results of this research explain that every community group has the same position in terms of rights and obligations as Indonesian citizens. with a sense of solidarity, tolerance and dialogue will further build a civilized and peaceful nation.